Impacto económico de las empresas comerciales de abarrotes en la ciudad de Calceta - Álava Bravo, Eder Jhon (2012)
This thesis was a study of the Economic Impact of the Commercial Companies of Groceries of the Cantón Bolívar; field in which the problem was identified, the authors proposed as general objective: To carry out a study of the economic impact suffered by the stores of groceries in the city of Stocking; and as specific objectives: To determine the number of stores of existent groceries in the City of Stocking; to characterize the stores of groceries; to estimate the economic impact suffered by the stores of groceries by means of a comparative square and the estimate of the price of the basic basket in the stores of groceries. To carry out the execution of these objectives it was applied two surveys, one focused to the citizenship of the Cantón Bolívar and another directed to Small Merchants. The results of this investigation contributed to make an effective study of the Economic Impact of the Commercial Companies of Groceries of the Cantón Bolívar.